THE 42\(nd\) INTERNATIONAL S.B. STECHKIN’S WORKSHOP-CONFERENCE ON FUNCTION THEORY - Vitalii V. Arestov; Vitalii I. Berdyshev (Ural Mathematical Journal)
The paper is devoted to the description of the history and results of the 42nd International S.B.Stechkin's Workshop on function theory, held in August 2017 in the Ilmen Nature Reserve near the town of Miass, Chelyabinsk region.